Hedging costs and joint determinants of premiums and spreads in structured financial products - Oliver Entrop; Georg Fischer (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2019)
This paper is the first to analyze the joint determinants of premiums and spreads in structured financial products, while also focusing on issuers' hedging costs. We evaluate more than 396,000 single stock discount certificates on an intraday basis in the German secondary market. We find that premiums and spreads are endogenous and negatively related to each other, and depend on different key determinants. The economically significant determinants of the premiums are mainly profit-related, i.e. dividends of the underlying, issuers' credit risk, lifecycle effect and competition, whereas hedging costs and risks are economically less important. However, initial hedging costs are also priced into the premium in the case of large inventory changes. The spread is mostly determined by hedging costs and risk components, such as initial hedging costs, rebalancing costs, volatility, scalper risk, and overnight gap risk, but also depends on dividends. Initial hedging costs appear to be more relevant than rebalancing costs.
Keywords: D40; G12; G21; 650; Discount certificates; Derivatives; Pricing; Market microstructure; Trading costs; Hedging